Mechanism, structural and functional insights into nidovirus-induced double-membrane vesicles - Wang, Xi; Chen, Yiwu; Qi, Chunyun; Li, Feng; Zhang, Yuanzhu; Zhou, Jian; Wu, Heyong; Zhang, Tianyi; Qi, Aosi; Ouyang, Hongsheng; Xie, Zicong; Pang, Daxin (Frontiers in Immunology, 2024)
During infection, positive-stranded RNA causes a rearrangement of the host cell membrane, resulting in spe-cialized membrane structures formation aid in viral genome replication. Double-membrane vesicles (DMVs), typical structures produced by virus-induced membrane rearrangements, are platforms for viral replication. Nidoviruses, one of the most complex positive-strand RNA viruses, have the ability to infect not only mam-mals and a few birds but also invertebrates. Nidoviruses possess a distinctive replication mechanism, wherein their nonstructural proteins (nsps) play a crucial role in DMV biogenesis. With the participation of host fac-tors related to autophagy and lipid synthesis pathways, several viral nsps hijack the membrane rearrangement process of host endoplasmic reticulum (ER), Golgi apparatus and other organelles to induce DMV formation. An understanding of the mechanisms of DMV formation and its structure and function in the infectious cycle of nidovirus may be essential for the development of new and effective antiviral strategies in the future.